2021
DOI: 10.1371/journal.pone.0256158
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: Epigenetics in Pregnancy (EPIPREG) – population-based sample of European and South Asian pregnant women with epigenome-wide DNA methylation (850k) in peripheral blood leukocytes

Abstract: Pregnancy is a valuable model to study the association between DNA methylation and several cardiometabolic traits, due to its direct potential to influence mother’s and child’s health. Epigenetics in Pregnancy (EPIPREG) is a population-based sample with the aim to study associations between DNA-methylation in pregnancy and cardiometabolic traits in South Asian and European pregnant women and their offspring. This cohort profile paper aims to present our sample with genetic and epigenetic data and invite resear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 57 publications
(69 reference statements)
0
32
0
Order By: Relevance
“…Global DNAm is altered during hyperglycemia ( 34 , 35 ), and increased global methylation in placental tissue has been associated with GDM ( 36 , 37 ). However, there are limited data describing DNAm in the peripheral blood of patients with GDM, and the results are inconclusive ( 16-19 , 21 , 22 , 38 , 39 ). Small sample sizes and the absence of reproducibility or confirmatory cohorts have been the main weaknesses in most studies ( 16-18 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global DNAm is altered during hyperglycemia ( 34 , 35 ), and increased global methylation in placental tissue has been associated with GDM ( 36 , 37 ). However, there are limited data describing DNAm in the peripheral blood of patients with GDM, and the results are inconclusive ( 16-19 , 21 , 22 , 38 , 39 ). Small sample sizes and the absence of reproducibility or confirmatory cohorts have been the main weaknesses in most studies ( 16-18 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on Black South African women, global DNAm in peripheral blood was found not to be associated with GDM, which was contrary to the authors’ hypothesis ( 20 ). Two studies with larger cohorts have been recently published using the Infinium MethylationEPIC BeadChip ( 21 , 22 ), which covers 850 000 CpG sites. Fragoso-Bargas et al ( 22 ) identified 4 CpG sites associated with BMI and hyperglycemia in peripheral blood leukocytes of a subcohort of the EPI-PREG study; however, the data were not validated in an independent cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technical validation was performed on four CpG sites preliminary associated with fasting glucose, 2-hour glucose and BMI. Overall, the four sites had a good agreement between pyrosequencing and the EPIC array [15].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously assessed genetic ethnic origin through ancestry principal component analysis by using the variance-standardized relationship matrix using PLINK 1.9. There was a clear separation between EUR and SA which corresponded to their inferred ancestry [15]. We, therefore, use self-reported ancestry for the categorization of ethnicity.…”
Section: Dna Methylation Profiling and Genotypingmentioning
confidence: 99%